2016
DOI: 10.1016/j.chroma.2016.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Retention behavior of isomeric polycyclic aromatic sulfur heterocycles in reversed-phase liquid chromatography

Abstract: Retention indices for 70 polycyclic aromatic sulfur heterocycles (PASHs) were determined using reversed-phase liquid chromatography (LC) on a monomeric and a polymeric C18 stationary phase. Molecular shape parameters [length, breadth, thickness (T), and length-to-breadth ratio (L/B)] were calculated for all the compounds studied. Correlations between the retention on the polymeric C18 phase and PASH geometry (L/B and T) were investigated for six specific PASH isomer groups with molecular mass (MM) 184 Da, 234 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…S1) on the structure. In a companion study [37] the LC retention behavior of the parent PASHs is reported, and this study demonstrated that the three- and four-ring unsubstituted PASHs eluted later than expected based on L/B when the sulfur atom was located in a bay-region of the structure. These observations suggest that when the sulfur atom is located in a bay -like-region, the sulfur atom is protected from from interacting with the stationary phase (C 18 ).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…S1) on the structure. In a companion study [37] the LC retention behavior of the parent PASHs is reported, and this study demonstrated that the three- and four-ring unsubstituted PASHs eluted later than expected based on L/B when the sulfur atom was located in a bay-region of the structure. These observations suggest that when the sulfur atom is located in a bay -like-region, the sulfur atom is protected from from interacting with the stationary phase (C 18 ).…”
Section: Resultsmentioning
confidence: 84%
“…LC retention measurements were recorded using the same instrumentation described in a companion publication on LC separation of parent PASHs [37]. Separations were performed on monomeric (Agilent 5) and polymeric (Zorbax Eclipse PAH) C 18 columns purchased from Agilent (Avondale, PA) with the following characteristics: 25 cm length, 4.6 mm diameter, and 5 μm average particle diameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, reversed-phase liquid chromatography (RPLC) on octadecylsilane (C 18 ) stationary phases has been shown to provide unique selectivity for separating isomeric PASHs [23–25]. However, GC still provides significantly greater separation capabilities over RPLC for determining PASHs in complex samples.…”
Section: Introductionmentioning
confidence: 99%
“…In a companion study, the same three stationary phases have been evaluated for the separation of alkyl-substituted PASHs [41]. A similar study has been published investigating the RPLC retention behavior and shape selectivity correlations for the same PASHs [23] and alkyl-substituted PASHs [24]. …”
Section: Introductionmentioning
confidence: 99%